POSS-containing hybrid nanomaterials based on thiol-epoxy click reaction. (6th June 2018) - Lungu, Adriana; Ghitman, Jana; Cernencu, Alexandra I.; Serafim, Andrada; Florea, Nicoleta M.; Vasile, Eugeniu; Iovu, Horia
Abstract: Organic-inorganic nanocomposites were designed by combining a commercial epoxy resin (diglycidyl ether of bisphenol A - DER) and a multi-thiol crosslinking agent with a "clickable" polyhedral oligomeric silsesquioxane (POSS) compound. 1-methylimidazole was employed as a catalyst to yield highly efficient thiol-Michael addition reaction materials. The equivalent ratio between epoxy: thiol was maintained 1:1 in all the formulations and therefore the homopolymerization reaction of epoxy resin is unlikely to occur. The synergistic effect of the thiol compound and mono-functionalized POSS bearing one epoxy/thiol reactive group on the curing process was investigated in detail. We assume that the mechanistic pathway of the thiol-epoxy click-reaction increases in complexity due to the introduction of reactive POSS in the system. The incorporation of mono-epoxy or mono-thiol POSS in the thiol–epoxy organic host leads to distinct thermo-mechanical behavior of the crosslinked networks due to the fact that the POSS compound will chemically interact in the click reaction. Graphical abstract: Highlights: Novel materials embodying nanometric POSS in the thiol–epoxy host are investigated. POSS compound acting as filler and macromer chemically engage in the click reaction. The type of "clickable" POSS modulate the thermomechanical properties of thermosets.